Pelatihan Manajemen Pemasaran Dengan Website Pada Penjahit Kain Rayon Di Kecamatan Blahbatuh Bali - Luh Putu Safitri Pratiwi; I Made Pasek Pradnyana Wijaya; Dedy Panji Agustino (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2022)
The sale of rayon clothing lately has had a big impact on rayon tailors. One of them is our community service partner, I. B Rai Sudipta, the owner of Bagus Rayon, which is located in Blahbatuh District, Gianyar Regency. Bagus rayon itself has been around for more than a year, but only has one supplier of rayon clothing in Gianyar Regency whose sales depend on that supplier. If the supplier experiences a decrease in sales, it will also have an impact on the volume of good rayon stitches, so our service team wants to provide marketing management training so that partner service businesses don't just depend on that one supplier and the marketing of good rayon is getting wider. For our own marketing, we provide training using online media, namely Instagram and the website. The series of training activities that will be carried out by the service team are: Socialization, Discussion on marketing design concepts, Training using Instagram and the Website, finally evaluation. From the evaluation results. partners can do marketing through the website so that they can expand the marketing area with the results of the evaluation using a questionnaire obtained an index value of 91.67% very good category.